2010
DOI: 10.1159/000320500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nilvadipine on Central Visual Field in Retinitis Pigmentosa: A 30-Month Clinical Trial

Abstract: Purpose: To assess the effects of nilvadipine on the progression of central visual field defect in retinitis pigmentosa (RP). Design: Prospective, randomized, nonmasked, single-center trial. Methods: Patients with RP were randomly divided into a treated group receiving oral nilvadipine at 4 mg/day for ≧30 months and a control group receiving tocopherol nicotinate at 300 mg/day, helenien at 15 mg/day or no medication for the same periods. Progression of RP was evaluated using the 10-2 SITA Fast Program of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 66 publications
0
42
0
5
Order By: Relevance
“…Identifier: NCT01399515). Some studies in animal models have shown that calcium channel blockers (e.g., diltiazem, nicardipine, nilvadipine, or nifedipine) inhibit photoreceptor degeneration (Frasson et al 1999;Takano et al 2004), and a 30-mo clinical trial recently reported that nilvadipine at 4 mg/d significantly retarded progression of central visual field defects in RP (Nakazawa et al 2011). …”
Section: Alternative Pharmacological Approachesmentioning
confidence: 99%
“…Identifier: NCT01399515). Some studies in animal models have shown that calcium channel blockers (e.g., diltiazem, nicardipine, nilvadipine, or nifedipine) inhibit photoreceptor degeneration (Frasson et al 1999;Takano et al 2004), and a 30-mo clinical trial recently reported that nilvadipine at 4 mg/d significantly retarded progression of central visual field defects in RP (Nakazawa et al 2011). …”
Section: Alternative Pharmacological Approachesmentioning
confidence: 99%
“…A second approach is to slow the degeneration of photoreceptors and thus slow progression of the disease. [13][14][15][16][17][18] Finally, there are a number of approaches that do not interfere with the intrinsic progression of disease but attempt to restore photosensitivity by creating new photosensors and coupling them to the remaining retinal circuitry. Patients who are legally blind are the key target population of these therapies.…”
Section: Potential Therapies For Retinitis Pigmentosamentioning
confidence: 99%
“…On the basis of the results from our previous study, Nakazawa and associates [8] reported that nilvadipine, a calciumchannel blocker, could delay the progression of visual dysfunction in eyes with RP, using the MD slope derived from the Humphrey 10-2 program in the 30-month followup period.…”
Section: Introductionmentioning
confidence: 99%